2019
DOI: 10.5334/aogh.2518
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Spatio-Temporal Patterns of Human Rabies Exposure in Northwestern Tigray, Ethiopia

Abstract: Background:Rabies is a neglected tropical disease, which is economically important with great public health concerns in developing countries including Ethiopia. Epidemiological information can play an important role in the control and prevention of rabies, though little is known about the status of the disease in many settings of Ethiopia. The present study aimed to investigate the risk factors and spatio-temporal patterns of human rabies exposure in Northwestern Tigray, Ethiopia.Methods:A prospective study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 36 publications
2
25
1
Order By: Relevance
“… 33 38 39 85 100 Dog vaccination coverage varied from 14.1% to 68.78%. 33 85 In Ethiopia and Zimbabwe, the dog vaccination decreased significantly across the study and also the health status of most dogs involved in biting was unknown. 39 100 Rabies prevention and control also depended on the seasonality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 33 38 39 85 100 Dog vaccination coverage varied from 14.1% to 68.78%. 33 85 In Ethiopia and Zimbabwe, the dog vaccination decreased significantly across the study and also the health status of most dogs involved in biting was unknown. 39 100 Rabies prevention and control also depended on the seasonality.…”
Section: Resultsmentioning
confidence: 99%
“…16 17 20 21 The review of 20 studies across Africa has revealed that bite victims account for 91.9% (48 092 dog bites), cat bite for 2.9%, jackal bite for 0.8% and 4.41% for others (monkey, donkey, horse, rat, pig, rabbit, Honey badger, kudu, goat, cattle, eland and hyaena). [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Mass vaccination of dogs as a key component of national rabies elimination programmes has been successful in eliminating dog-transmitted rabies in Europe, North and Latin America, and Japan. [49][50][51] By far, the most significant public health threat comes from RABV, and over 99% of all globally reported human cases are caused by exposure to unvaccinated dogs infected with canine RABV variant, mostly in Asia and Africa.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In rural areas, the preferential use of traditional/spiritual healers might also contribute to the reduced level of post-exposure prophylaxis (PEP) ( 14 ). Based on registered health records, the annual human rabies exposure rate (based on refined exposure risk assessment performed following rabies suspected animal bite) per 100,000 population has been estimated to range from zero to 40 ( 15 , 16 ). To account for underreporting, Beyene et al ( 17 ) conducted an extensive survey-based case search, also known as contact tracing.…”
Section: Health and Economic Burden Of Rabiesmentioning
confidence: 99%
“…It helps the decision-making to determine the allocation of limited medical and human resources and the preparedness for the infection control measures, especially for developing countries. Detection of disease clustering contributes to identification of risk factors for exposure [ 8 ] as well as identification of the signals of a pandemic [ 9 ]. Several previous studies using spatiotemporal analysis have contributed to decision-making during outbreaks of emerging infectious diseases such as severe acute respiratory syndrome (SARS) [ 10 ], Middle East respiratory syndrome [ 11 ], avian influenza A (H5N1) [ 12 ] and (H7N9) viruses [ 13 ] infections and COVID-19 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%